Tunnelling in molecules nuclear quantum effects from bio to physical chemistry - Kästner, Johannes 1978-; Kozuch, Sebastian (Royal Society of Chemistry, RSC, 2021)
Cover -- Preface -- Contents -- Chapter 1 Direct Observation of Tunnelling Reactions by Matrix Isolation Spectroscopy -- 1.1 Introduction -- 1.2 Description of Simple Mathematic Models for Tunnelling Computations -- 1.3 The Matrix Isolation Method: Creating the Conditions for Direct Observation of Tunnelling-driven Chemistry -- 1.4 Interpretation of Kinetic Decays Observed in Cryogenic Matrices -- 1.5 NIR and IR-induced Chemistry -- 1.6 Conformational Isomerizations by Tunnelling -- 1.7 Bond-breaking/Bond-forming H-atom Tunnelling (H-shifts) -- 1.8 Heavy-atom Tunnelling
Keywords: Tunneleffekt; Molekülsystem; Aufsatzsammlung